THE IMPACT OF THE COGNITIVE LEARNING CYCLE STRATEGY ACCORDING TO BLOOM’S TAXONOMY AND ITS REFLECTION ON DEVELOPING THE THEORETICAL TEACHING METHODS COURSE FOR SECOND STAGE STUDENTS - Asst. Prof. Dr. Hazem ALI CHazee (Galaxy International Interdisciplinary Research Journal, 2024)
The aim of the study is to investigate the impact of the cognitive learning cycle strategy on cognition, based on each phase of the cycle (exploration phase, concept introduction phase, concept application phase, and concept evaluation phase). The study combines learning strategies and metacognitive strategies to enhance awareness and critical thinking among the study sample. The significance of the study lies in providing students with the opportunity to rely on their own prior knowledge and retrieve it when applying the educational curriculum prepared by the researcher. The curriculum includes diverse teaching units based on the curriculum content. The researcher constructed a cognitive achievement scale for the theoretical teaching methods course, consisting of 57 items. The study population consisted of second-year students at the College of Physical Education and Sports Sciences, University of Al-Qadisiyah, for the academic year 2022-2023. The study sample included 40 students, divided into control and experimental groups. The study lasted for ten weeks, with one teaching unit per week. After implementing the educational curriculum, a cognitive achievement test was administered to the study sample within the classrooms. The results were collected for statistical analysis.